2018
DOI: 10.1111/ggi.13461
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sarcopenia and depression in older patients with diabetes: An investigation using the Japanese version of SARC‐F

Abstract: A statistically significant relationship was shown between sarcopenia and depression in older male patients with diabetes. We believe that drawing the attention of physicians to sarcopenia prevalence by using the Japanese version of SARC-F will contribute to the detection of depression in older male patients with diabetes. Geriatr Gerontol Int 2018; 18: 1318-1322.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
(89 reference statements)
2
12
1
1
Order By: Relevance
“…For example, in a recent study involving Japanese adults, decreased muscle mass (sarcopenia) was related to depression in older men with diabetes but not in older women. 13 Contrary to these previous studies, our data indicated that depressive mood was inversely associated with chair stand test performance, gait speed and standing balance test performance in both men and women. This difference in results might be explained by the inclusion of relatively 'young' older subjects (the average age was no more than 70 years), by the low severity of the reported depression or the small sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…For example, in a recent study involving Japanese adults, decreased muscle mass (sarcopenia) was related to depression in older men with diabetes but not in older women. 13 Contrary to these previous studies, our data indicated that depressive mood was inversely associated with chair stand test performance, gait speed and standing balance test performance in both men and women. This difference in results might be explained by the inclusion of relatively 'young' older subjects (the average age was no more than 70 years), by the low severity of the reported depression or the small sample size in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…12 In addition, a statistically significant relationship was observed between sarcopenia and depression in older male patients with diabetes. 13 A recent study involving Japanese urban-dwelling older adults revealed that depressive mood was not associated with decreased muscle mass but was associated with low muscle strength and low physical performance. 14 In contrast, results from the 2010-2011 Korean National Health and Nutrition Examination Survey showed that sarcopenia was not associated with depression in Korean adults.…”
mentioning
confidence: 98%
“…Primary sarcopenia is largely attributable to aging, while secondary sarcopenia can occur earlier in life in association with a range of other conditions [12,13]. Recent evidence showed that sarcopenia was positively associated with depressive symptoms assessed by self-rating scales among different populations, such as community-dwelling people and patients with type II diabetes, hemodialysis, end-stage kidney disease and cancer [14][15][16][17]. Sarcopenia, suicide and depression share common risk factors, such as chronic low-grade inflammation, brain-derived neurotropic factor (BDNF) dysfunction and dysregulated hypothalamic-pituitary-adrenal (HPA) axis [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence showed that sarcopenia was positively associated with depressive symptoms assessed by self-rating scales among different populations, such as community-dwelling people and patients with type II diabetes, hemodialysis, end-stage kidney disease and cancer [14][15][16][17].…”
mentioning
confidence: 99%